Norte precario : poblamiento y colonización en México (1760-1940) - Aboites, Luis (Book collections on Project MUSE., 1995)
"Study of the main territorial occupation and population trends of the vast region of northern Mexico. Studies commercial routes, mining development, indigenous resistance, and infiltration of North American capitalist enterprises to determine population policies between the 18th- and mid-20th centuries"--Handbook of Latin American Studies, v. 58.